Protein tyrosine phosphatase 1B in metabolic and cardiovascular diseases: from mechanisms to therapeutics - Sun, Yan; Dinenno, Frank A.; Tang, Peiyang; Kontaridis, Maria I. (Frontiers in Cardiovascular Medicine, 2024)
Protein Tyrosine Phosphatase 1B (PTP1B) has emerged as a significant regulator of metabolic and cardiovascular disease. It is a non-transmembrane protein tyrosine phosphatase that negatively regulates multiple signaling pathways integral to the regulation of growth, survival, and differentiation of cells, including leptin and insulin signaling, which are critical for development of obesity, insulin resistance, type 2 diabetes, and cardiovascular disease. Given PTP1B's central role in glucose homeostasis, energy balance, and vascular function, targeted inhibition of PTP1B represents a promising strategy for treating these diseases. However, challenges, such as off-target effects, necessitate a focus on tissue-specific approaches, to maximize therapeutic benefits while minimizing adverse outcomes. In this review, we discuss molecular mechanisms by which PTP1B influences metabolic and cardiovascular functions, summarize the latest research on tissue-specific roles of PTP1B, and discuss the potential for PTP1B inhibitors as future therapeutic agents.